2002
DOI: 10.1046/j.1365-2591.2002.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro comparison of pH changes in root dentine following canal dressing with calcium hydroxide points and a conventional calcium hydroxide paste

Abstract: The results of this study indicate that an aqueous calcium hydroxide paste was more effective than calcium hydroxide points at raising the pH on the external root surface of extracted teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
1
22
1
Order By: Relevance
“…Our study found no additional benefit of CH compared with no lining. Moreover, we did not find significant differences between setting and non-setting CH, which have been thought to release different quantities of ions at different pH, thus exerting differential effects [43]. For CH, we thus accept our null hypothesis.…”
Section: Discussionsupporting
confidence: 47%
“…Our study found no additional benefit of CH compared with no lining. Moreover, we did not find significant differences between setting and non-setting CH, which have been thought to release different quantities of ions at different pH, thus exerting differential effects [43]. For CH, we thus accept our null hypothesis.…”
Section: Discussionsupporting
confidence: 47%
“…3 The efficiency of the antibacterial action is directly proportional to the ability of the hydroxide ions to diffuse from the hydroxide compound. However, researches suggest that the filling of root canals with Ca(OH) 2 might weaken endodontically treated teeth.…”
Section: Introductionmentioning
confidence: 99%
“…In a water suspension, less than 0.2% of the powder is dissolved into calcium and hydroxyl ions. Because it is a powerful alkaline, this results in a paste with a pH of approximately 12.5 (Ardeshna et al 2002). This pH is sufficient to kill on contact most bacterial root canal species (Byström et al 1985).…”
Section: Introductionmentioning
confidence: 99%